Minichromosome Maintenance Proteins: From DNA Replication to the DNA Damage Response - Agnes Malysa; Xiaohong Mary Zhang; Gerold Bepler (Cells)
The DNA replication machinery is highly conserved from bacteria to eukaryotic cells. Faithful DNA replication is vital for cells to transmit accurate genetic information to the next generation. However, both internal and external DNA damages threaten the intricate DNA replication process, leading to the activation of the DNA damage response (DDR) system. Dysfunctional DNA replication and DDR are a source of genomic instability, causing heritable mutations that drive cancer evolutions. The family of minichromosome maintenance (MCM) proteins plays an important role not only in DNA replication but also in DDR. Here, we will review the current strides of MCM proteins in these integrated processes as well as the acetylation/deacetylation of MCM proteins and the value of MCMs as biomarkers in cancer.